2013
DOI: 10.1080/1059924x.2013.839977
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Ergonomic Evaluation of Barn Tasks in Intensive Swine Production

Abstract: This exploratory pilot study analyses musculoskeletal symptoms and working exposures of intensive pig barn tasks. Methods included a questionnaire phase to gather information about workers' symptoms and video analysis to assess exposures during typical production tasks. Ninety-two percent of workers reported symptoms in the last 12 months in any body part; 58% reported interruption of work activities in the last 12 months. The task "moving dead pigs" exceeded 3400 N during 6 of 18 observations. Frequency of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The need for ergonomic interventions has been identified for agriculture in general [ 17 , 54 ] and within the pig industry in particular [ 5 ], but few have been systematically evaluated. Intervention research is the primary avenue for research-to-practice translation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for ergonomic interventions has been identified for agriculture in general [ 17 , 54 ] and within the pig industry in particular [ 5 ], but few have been systematically evaluated. Intervention research is the primary avenue for research-to-practice translation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Danish swine workers were also found to have high rates of MSD [ 4 ]. A recent pilot study of workers in the Canadian swine industry found a 12-month prevalence of 92% of MSD and 58% of respondents reported having their activities interrupted by MSD symptoms [ 5 ]. Such disorders are the most common cause of work absence in self-employed Dutch farmers [ 6 ], and Irish farm income is shown to be lower when operators have MSD-related disability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many agricultural tasks are labor intensive and performed over long periods of time with little alterations in position. [24][25][26] These repetitive tasks are of particular concern in the dairy industry, where dairy workers maintain a certain position during milking due to the engineering setup of the barn (i.e., parallel versus herringbone [ Figure 1] versus rotary parlor systems in addition to the stanchion system used by many smaller farms [ Figure 2]). 19,[27][28][29] Such systems are useful for milking many cows but are not conducive to worker ergonomics, especially if the worker has sustained a repetitive stress injury related to milking procedures.…”
Section: Workers' Compensationmentioning
confidence: 99%
“…2 Within the last few decades, animal husbandry has evolved from traditional family farms to larger intensive operations with many more animals and workers per barn. This change has increased task specialization 3 and potentially the number of hours that workers are exposed to contaminants, including H 2 S. H 2 S exposure can cause dizziness and irritation of the respiratory tract, 1 and at high concentrations it can produce deadly incidents within these livestock facilities, with 77 fatalities between 1975 and 2004. 4 However, health effects at low exposure levels are not as well understood nor documented.…”
Section: Introductionmentioning
confidence: 99%